Investigation of Vibration Energy Harvesting in Multilayer Composite Plates with Anisotropic Piezoelectric Patches - Asghar Jamshiddoust; Morteza Karamooz Mahdiabadi; Amin Farrokhabadi (Mechanics of Advanced Composite Structures)
This study investigates the impact of anisotropic and isotropic piezoelectric coefficients on vibrational energy harvesting using a piezoelectric patch integrated into plate-like structures. The research on energy harvesting in such configurations has garnered substantial attention in recent decades, with previous studies typically assuming isotropic piezoelectric coefficients (e_31=e_32). The investigation focuses on two common boundary conditions: cantilevered composite plate (CFFF) and all-four-edges clamped (CCCC), employing a combination of analytical techniques and numerical simulations. The study presents comprehensive steady-state formulations for both the electrical and structural responses under harmonic force excitation. By comparing the voltage-frequency relationship between the analytical and numerical models, the accuracy of the analytical electroelastic model is verified. The findings highlight the potential for enhanced performance and increased output voltage in CFFF structures with an approximate rate between 5% to 8 % by minimizing the impact of the e_32 coefficient, whereas a decrease in output voltage is observed in CCCC structures. The findings emphasize that minimizing the impact of specific piezoelectric coefficients can lead to significant improvements in both performance and output voltage. This contributes to advancements in energy harvesting technology, highlighting the importance of optimizing piezoelectric materials to achieve better efficiency in energy harvesting applications. Additionally, the study shows that reducing the effects of e_32 in anisotropic piezoelectric harvesters can enhance energy harvesting from the vibration of a multilayer composite cantilevered plate. This research contributes valuable insights into optimizing piezoelectric energy harvesting efficiency in plate-like structures, paving the way for advancements in energy harvesting technology.